2016
DOI: 10.1093/geront/gnw156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fall Prevention on Nurses and Care of Fall Risk Patients

Abstract: Results of this study identify unintended consequences of fall prevention message on nurses and older adult patients. Further research is needed understand how nurse care for fall risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 24 publications
2
84
0
3
Order By: Relevance
“…The review yielded 23 articles that represented one mixed methods (Strumpf & Evans, ), seven quantitative (Farina‐Lopez, Estevez‐Guerra, Polo‐Luque, Pogranyiva, & Penelo, ; Janelli, Stamps, & Delles, ; Liukkonen & Laitinen, ; McCabe, Alvarez, McNulty, & Fitzpatrick, ; Myers, Nikoletti, & Hill, ; Suen et al, ; Werner, ) and 15 qualitative studies (Bok, Pierce, Gies, & Steiner, ; Boltz, Capezuti, & Shabbat, ; Brown, Williams, Woodby, Davis, & Allman, ; Chuang & Huang, ; Dahlke, Hall, & Baumbusch, ; Dahlke & Phinney, ; Goethals, Dierckx de Casterlé, & Gastmans, ; King, Pecanac, Krupp, Liebzeit, & Mahoney, ; Kneafsey, Clifford, & Greenfield, ; Lai, ; Lee, Chan, Tam, & Yeung, ; Ludwick, O'Toole, & Meehan, ; Nolan, ; Quinn, ; Schofield, Tolson, & Fleming, ). Nine were conducted in the United States, three in the United Kingdom, three in Hong Kong, two in Canada and one each in Spain, Taiwan, Belgium, Finland, Australia and Israel.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The review yielded 23 articles that represented one mixed methods (Strumpf & Evans, ), seven quantitative (Farina‐Lopez, Estevez‐Guerra, Polo‐Luque, Pogranyiva, & Penelo, ; Janelli, Stamps, & Delles, ; Liukkonen & Laitinen, ; McCabe, Alvarez, McNulty, & Fitzpatrick, ; Myers, Nikoletti, & Hill, ; Suen et al, ; Werner, ) and 15 qualitative studies (Bok, Pierce, Gies, & Steiner, ; Boltz, Capezuti, & Shabbat, ; Brown, Williams, Woodby, Davis, & Allman, ; Chuang & Huang, ; Dahlke, Hall, & Baumbusch, ; Dahlke & Phinney, ; Goethals, Dierckx de Casterlé, & Gastmans, ; King, Pecanac, Krupp, Liebzeit, & Mahoney, ; Kneafsey, Clifford, & Greenfield, ; Lai, ; Lee, Chan, Tam, & Yeung, ; Ludwick, O'Toole, & Meehan, ; Nolan, ; Quinn, ; Schofield, Tolson, & Fleming, ). Nine were conducted in the United States, three in the United Kingdom, three in Hong Kong, two in Canada and one each in Spain, Taiwan, Belgium, Finland, Australia and Israel.…”
Section: Resultsmentioning
confidence: 99%
“…In 2 of the studies, nursing staff in the United States (US) (Janelli et al, ) and the United Kingdom (UK) (Schofield et al, ) discussed using chemical restraints to keep their older patients from harms that were defined as falling or removing medical equipment (e.g., catheters, intravenous lines). Studies from Taiwan (Chuang & Huang, ), Spain (Farina‐Lopez et al, ), the United States (King et al, ; Ludwick et al, ; McCabe et al, ; Quinn, ; Strumpf & Evans, ), Hong Kong (Lai, ; Lee et al, ; Suen et al, ), Finland (Liukkonen & Laitinen, ), Australia (Myers et al, ) and Israel (Werner, ) all reported nurses' use of physical restraints to keep their older patients safe. Four of the studies identified that once physical restraints had been applied to an older patient, nursing teams were reticent to remove them, even if the reason for using the restraint was no longer present (Chuang & Huang, ; Goethals et al, ; Ludwick et al, ; Suen et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hospitalized older adults are especially vulnerable to functional decline due to age-related changes in cardiovascular and musculoskeletal systems. Decreased ambulation due to illness, staffing issues, and nurses' fear of patients falling can result in increased functional decline and an increased risk for falling while in the hospital (King, Steege, Winsor, & VanDenbergh, 2016) and after discharge to the community (King, Pecanac, Krupp, Liebzeit, & Mahoney, 2016).…”
Section: Implications For Nursing Practicementioning
confidence: 99%